(3LGeY GdeHGfj aj TQM abg GdcjOGfjs - (3GdNQGSGfj GdbgSJGfj, eMeO Hf MSGe GdOjf, J (B962 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj QaY bGYOI Gdabg CeG HYO adeG Cf JMd ef gPg GdOGQ NjGQ gPg GdCeI GdCHQGQ Ke LeY efge hef cJHge JdGePJge aj GdePgH GdMfaj Gdehdi dWa Gddg GdfSaj GdcjOGfjs
(3BNQgG (B:s
(3haj GdJYeO ETYGQ HCfg de jHdZg Edi GdEJeGe hdYd gPG GdjSjQ fGaY ddCfGe HMQeI GdfHj Ydjg GdUdhI hGdSdGe eG CfLR GdGaJJGM HGdGNJJGes
(3hgj efShHI Edi TeS GdOjf GdafGQj eMeO Hf MeRI ceG UQM Hg TGQMgG CMeO WGTcHQj RGOg GdeJhai SfI (B968 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 11s
(3eYLe GdeDdajf (B3 / 211s
(3cTa GdXfhf (B2 / 1802s
(3gOjI GdYGQajf (B2 / 244s
Keywords: (3Gdabg GdMfHdjs